A comparison of spleen size measured by ultrasound in a random population sample and a matched sample of patients at a university hospital, and the determination of normal values and influencing factors - Schranz, Theresa; Klaus, Jochen; Kratzer, Wolfgang; Schmidberger, Julian; Güthle, Melanie (Zeitschrift für Gastroenterologie, 2021)
Objectives This study aimed to compare spleen sizes in a hospital and a population sample using ultrasound and define normal values and factors influencing spleen size.Methods Both samples’ spleen sizes (n = 1520) were measured using ultrasound under the same conditions. Blood counts and other laboratory parameters were determined under the same conditions in both samples.Results In the hospital sample (n = 760), the mean spleen size was 114.7 mm, and in the population sample (n = 760), it was 99.1 mm. In both, spleen size in men was significantly higher than in women (p < 0.0001) and influenced by body height, weight, and BMI (body mass index) (p < 0.0001). In the hospital sample, there was a correlation with higher values for ALT (p = 0.0160), AST (p = 0.0394), AP (p = 0.0482), and ferritin (p = 0.0008) and lower values for HDL (p = 0.0091) and thrombocytes (p < 0.0001). In the multivariate analysis, higher values for AP (p = 0.0059) and lower values for hemoglobin (p = 0.0014) and thrombocytes (p = 0.0001) were found. Stratified for sex (men, women), spleen size increased with higher values for ALT (p = 0.0116, p = 0.0113), AST (p = 0.0014, p = 0.0113), and AP (p = 0.0001, p = 0.0012), and with lower values of hemoglobin (p = 0.0057, p = 0.0016), thrombocytes (p < 0.0001, p = 0.0003), and albumin (p = 0.0029, p = 0.0432). In women, there was a discordant correlation with red blood cells (p = 0.0005) and a concordant correlation with GGT (p = 0.0241), and in men discordant correlations with cholesterol (p = 0.0010) and HDL (p = 0.0404).Conclusions The already proven impact of anthropometric data on spleen size was confirmed. The role of laboratory values should be further analyzed.
Keywords: spleen; ultrasound; size; reference values; risk factors